Comparative analysis of the compressive strength of concrete under different curing methods. Issue 1 (March 2021) - Murillo, M; Abudinen, D; Río, M del; Serrato, N; Patrón, L; Ramírez, J
Abstract: Concrete is the most widely used material in construction, which possesses different characteristics and possible manufacturing methods. Concrete is, also, characterized by its high resistance to compression and durability, factors that could have been directly influenced by the curing method in early ages. The objective of this research is to demonstrate the importance of the concrete curing process, as well as to analyze the influence of the chosen curing method on the compression resistance. 48 concrete test samples were manufactured, by the standard requirements. Subsequently, the samples were divided into eight batches, subjected to different types of curing: immersion curing, twice a day; outdoor curing; total immersion curing in different waters, application of commercial curing agent; with polyethylene foil coating and without curing. Performing compression testing at 7 and 28 days. Among the results obtained, the batch that underwent the method of curing with polyethylene coating presented a more efficient effect in terms of resistance to compression; followed by the techniques of immersion in water.